“Disciplinary didactics” in the Swiss Journal of educational research.: An analysis of 20 years of publications (2000-2020) - Aeby Daghé, Sandrine; Schneuwly, Bernard (Swiss Journal of Educational Research, 2021)
Starting from a broad definition of didactics, this article delineates a series of five dimensions to establish a global picture of the disciplinary field of didactics, based on disciplinary didactics publicationsin the Swiss Journal of educational research: reference culture of the texts; thematic focal points in the field of didactics ; whether or not a specifically didactic framework is mobilized; school disciplines addressed ; research methods implemented. In concrete terms, eight editorials and 82 contributions are the subject of quantitative and content analysis. The results show different trends in the articles from German and French didactic cultures: number of articles published, relationship to educational sciences, reference to specialized didactic literature, importance given to interventions and action research. The main school subjects are all represented, with a strong focus on the first language in German where physical education is lacking. The Journal thus profiles itself as a place of encounter, interaction and dialogue between different disciplinary didactics from different cultures.